An Isolated Osseous Rosai-Dorfman Disease Shown on FDG PET/CT. (June 2019) - Zadeh, Mahdi Zirakchian; Wen, Zhe; States, Lisa J.; Zhuang, Hongming
Abstract : Abstract: Rosai-Dorfman disease is typically presented as lymphadenopathy, especially in the neck. Extranodal diseases also frequently occur but are generally concurrent with nodal disease. We report FDG PET/CT findings of solitary femoral Rosai-Dorfman disease without any lymphadenopathy in a pediatric patient.